ASSESSMENT OF THE RESIDUAL LIFE-TIME OF THE ELEMENTS OF THE CENTRIFUGAL PUMP OF THE ENERGY INSTALLATION ON THE BASIS OF STATISTICAL ASSESSMENT OF FATIGUE WITH PREDICTED WEAR DUE TO CORROSION - LARIN, Oleksiy; POTOPALSKA, Ksenia; GRINCHENKO, Yevgen (Herald of Khmelnytskyi National University. Technical sciences, 2022)
In this article, the residual resource of a centrifugal pump was anticipated, which operates an overestimated resource in the pumping line of a nuclear power plant. The results of theoretical and numerical modeling of its stress-strain state with a change in the geometry of the hull parts are presented. Three-dimensional FE models have been developed that take into account the actual geometry of pump parts, as well as a forecast of their possible changes during further operation. The change in the geometry of the structure is taken into account on the basis of extrapolation of data on the thickness of the hull walls obtained over a long service life. Calculations to determine the static strength are made for the main operating mode of the pump (under normal operating conditions). In places of welds, the cyclic strength was checked separately, while taking into account the decrease in their strength due to an increase in equivalent stress amplitudes by dividing them by the coefficient of reduction in the strength of the weld. The process of thinning of the wall of the pump housing under the action of erosive-corrosive wear is modeled. This process is random, so it was modeled taking into account the equations of wear growth kinetics. As a result of the research, the damage parameter and the probability of failure-free operation of the structure were obtained. These parameters are determined taking into account the predicted values of the percentage thinning of the pump housing wall and the obtained characteristics of the statistical deformation state of the structure.